Optimization of the key position parameters for tractor steering wheel based on a driver’s arm muscle load analysis - Xu, Hongmei; Yang, Hao; Shang, Yujun; Zhang, Yinpei; Liu, Zhangfen; Wang, Qichao; Zhang, Guozhong (International Journal of Agricultural and Biological Engineering, 2023)
Steering wheel is the most frequently used manual device in tractors, whose position directly affects the handling comfort of the driver and fatigue degree of the arm muscles. In this study, the biomechanical modelling software AnyBody was used for an inverse kinetics analysis of the rotation process of tractor steering wheel, calculate the muscle activation degree of the driver's arm and compare it with the calculated results of surface EMG tests to verify the reliability of the biomechanical model. Based on the biomechanical model, the effects of three position parameters (steering wheel inclination, front-back distance, and upper-lower height) on the activation degree of the driver's arm muscles were evaluated. The results demonstrated that steering wheel inclination has the most significant effect on the degree of muscle activation, followed by the upper-lower height and then front-back distance. Considering the interaction among factors, a regression orthogonal test was designed, and the test results revealed that the minimum muscle activation (1.2887) can be obtained with the steering wheel inclination of 31°, front-back distance of 431 mm and upper-lower height of 375 mm. The findings can provide a reference for optimizing the structure and position parameters of tractor steering wheels. Key words: tractor, steering wheel, driver's arm, biomechanical characteristics, position parameter optimization DOI: 10.25165/j.ijabe.20231605.7996 Citation: Xu H M, Yang H, Shang Y J, Zhang Y P, Liu Z F, Qichao Wang, et al. Optimization of the key position parameters for tractor steering wheel based on a driver's arm muscle load analysis. Int J Agric & Biol Eng, 2023; 16(5): 236-247.